Intelligent Spraying Water Based on the Internet of Orchard Things and Fuzzy PID Algorithms. (25th April 2022) - Zhang, Pingchuan; Wang, Sijie; Bai, Menglong; Bai, Qiaoling; Chen, Zhao; Chen, Xu; Hu, Yanjun; Zhang, Jianming; Li, Yulin; Hu, Xueqian; Shi, Yiran; Deng, Jiajun
Abstract : During the fruit ripening period, the orchard temperature difference between day and night has a substantial impact on the fruit quality, and it is not easy to be controlled like that of in greenhouse, this paper designed the smart orchard Internet of Things (IoT), through the fuzzy PID (Proportion-Integration-Differentiation) algorithm to control the water spraying to adjust the temperature difference Δ T between day and night in the orchard, intelligently influenced the orchard energy conversion process, and promoted the fruit sugar accumulation. Experiments show that the maximum Δ T can reach 20°C, the intelligent energy regulation based on the IoT has a good effect, and a scheme to intervene the microclimate in farmland (quite different from the greenhouse environment) is provided.